Comitês de ética em pesquisa no âmbito latino-americano (Brasil-Argentina): transdisciplinaridade em prol da dignidade humana - Woltmann, Angelita (2006)
This is not the first time we hear about aggression to the environment and to man himself. It is, although, from the rising of globalization and a society of risks that such trouble begins to look like reality, specially in developing countries, such as the ones from Latin America. The human being nowadays is going through an uncomfortable feeling caused by his own behavior and it is reflected in the biomedical research area, which has more and more specialized techniques and professionals, who many times ignore the natural vulnerability of the Latin American research and put aside the ethics which should guide their research. Based on this crises of conscience or perception, there is the objective of studying transdisciplinarity in the Ethics in Research Committees as a new possible paradigm for the solution of bioethics controversies in biomedical research with human beings in Latin America. The study focus on Brazil and Argentina Committees. The research is based not only on theoretical considerations on bioethics, human dignity and transdiciplinarity but also on the systemic interpretation of Latin American reality. Therefore, the methodological approach has three perspectives: on its nature the research is basic; on its objectives it is exploitative; and from the object point of view, it is qualitative. Bibliographic and documental research is used considering the theoretical character of the study, having as theoretical reference, the ideas of Edgar Morin, Fridjof Capra and Volnei Garrafa. The question does not lie in being against or in favor of development, but to establish What is the kind of science we want. That is, through the transdisciplinar dialogue of the Ethics Committees from Latin American institutions, to make the scientific community aware that the bioethics principiology specially the human dignity principle is essential in the biomedical research field, or we shall harm not only the individual rights of the researched but also the right to health, which is inherent to society. Even if the practical solution is still far away, it is essential to (re)think the relationship man-science transdisciplinarly, so that a new human conscience is introduced, preoccupied in respecting human dignity and nature as a whole.